2015
DOI: 10.4102/phcfm.v7i1.608
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of active pulmonary tuberculosis in Ambo Hospital, West Ethiopia

Abstract: ObjectivesThe aim of this study was to determine factors associated with active pulmonary tuberculosis seen in cases in Ambo Hospital, Ethiopia.DesignA facility-based prospective case-control study.SettingPatients attending Ambo Hospital from 01 December 2011 to 29 March 2012.ParticipantsThe sample included 312 adult patients attending Ambo Hospital. The main outcome measure was presence of active pulmonary tuberculosis (TB).Explanatory measuresAge, gender, occupation, educational status, marital status, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
5
8
3
Order By: Relevance
“…However, communitybased study done in high burden settings in Ethiopia [15] and Philippines [27] showed significant association of older age groups with the presence of TB. Similarly, occupational status of the household contacts were not significantly associated with the occurrence of TB in this study which is inconsistent with the study conducted in West Ethiopia [17]. is might be due to difference with study participants, lifestyle, and socioeconomic factors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, communitybased study done in high burden settings in Ethiopia [15] and Philippines [27] showed significant association of older age groups with the presence of TB. Similarly, occupational status of the household contacts were not significantly associated with the occurrence of TB in this study which is inconsistent with the study conducted in West Ethiopia [17]. is might be due to difference with study participants, lifestyle, and socioeconomic factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Methods. Data were collected using a structured questionnaire developed from previous literature [15][16][17] and it was pretested on 5% of the study participants in a nearby district (i.e., Aweday district). Data collectors and supervisors were trained on data collection tools and how to observe measure, collect, and transport samples to health facility that helped minimize bias, and maintain the quality of data.…”
Section: Data Collection Tools Andmentioning
confidence: 99%
“…This result confirms what has been observed elsewhere in the world. The same risk was observed during studies conducted in Africa especially in Zambia [14], Malawi [29], Ethiopia [5] and Gambia [30]. In the USA, the risk was 1.7 [11].…”
Section: Discussionsupporting
confidence: 77%
“…In another view, sometimes, treatment is proposed empirically based on clinical and radiological arguments. Studies conducted worldwide have identified several risk factors associated with the occurrence of EPTB: age [1,2,9], female sex [1,11,12], no vaccination [13], contact with TB patient [5,12,14], alcohol consumption [11,15], employment [13,16], diabetes [15] and HIV infection [1,11] particularly. Senegal, like many Sub-Saharan African countries, is facing the TB epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the respondents were residing in rural settlements (39.1%), while 36.5% of TB patients resided in urban settlements. These findings were supported by the study of Ephrem et al, 18 which shows that the environmental risk factors, economic factors, and attitudes and behaviour associated with the spread of TB. In this study people living with TB are in the age brackets 34-40 years and 26-33 years, which is to say that the young economically productive age groups suffer more from tuberculosis.…”
Section: Discussionsupporting
confidence: 66%